The Role of Proteome in Cellular Zn2+ Trafficking and in the Ability of the Fluorescent Zinc Sensors to Image Intracellular Zn2+ - (:unkn) unknown (My University, 2016)
Zinc is an essential biological trace metal used in as many as 3000 Zn-proteins, about 10% of the eukaryotic proteome, as either a structural constituent or a catalytic cofactor. These proteins include the zinc fingers, the most prevalent transcription factors that bind a wide range of gene promoters and thus regulate gene expression. A eukaryotic cell contains several hundred micromolar of Zn2+- almost all of it is bound to specific Zn-proteins. Recently, Zn2+ has been reported to serve as a regulatory signal and a neurotransmitter, suggesting that there also exists a dynamic Zn2+ pool in cells. These findings led to the synthesis of a wide range of fluorescent sensors to image intracellular mobile Zn2+. Despite extensive knowledge about thousands of Zn-proteins, the Zn2+ trafficking pathway from its entry into the cytosol by transporters to the formation of Zn-proteins is not well understood. This present work has studied the role of proteome in cellular Zn2+ trafficking using fluorescent zinc sensors, including FluoZin-3, Zinquin (ZQ), TSQ, Newport Green (NPG) and Zinpyr-1 (ZP1). The titration of proteome pre-treated with FluoZin-3, a relatively high affinity Zn2+ sensor with the stability constant of 15 nM, with Zn2+ has revealed that proteome contains a significant number of high affinity, non-specific Zn2+ binding sites, with the stability constants on the order of 10-10 M. The discovery of these high affinity binding sites of proteome suggested that along with Zn-metallothionein, proteome too can serve as a possible intermediate along the way to the formation of native Zn-proteins. Moreover, this finding raises the question how the majority of the fluorescent zinc sensors with the stability constants ranging from micromolar to nanomolar image intracellular labile Zn2+ by circumventing the proteome’s high zinc buffering capacity. Interestingly, the thiol binding reagents, N-ethylmaleimide (NEM) and DTNB abolished these high affinity sites, revealing the involvement of proteomic sulfhydryl groups in these Zn2+ binding sites. The loss of proteome’s zinc buffering capacity upon sulfhydryl modification can explain how the sensors bind the dynamic Zn2+ pool by surpassing the proteome’s high Zn2+ binding affinity. For example, Zinquin, a high affinity sensor with Kd of 2 nM, could bind the mobile Zn2+ only when the proteome was significantly modified by the reaction under investigation, such as the liberation of proteomic Zn2+ by nitric oxide, which reacts with the sulfhydryl groups and thus reduces proteome’s buffering capacity. In case of unperturbed proteome, these sensors either are unable to compete for mobile Zn2+ with proteome’s high affinity Zn2+ binding sites or generate ternary adduct, Proteome•Zn-Sensor, with Zn2+ preferentially bound to proteome. Newport Green, for example, with its modest stability constant (Kd  10-5 – 10-6 M) cannot efficiently compete with proteomic ligands to image mobile Zn2+. It could not bind intracellular Zn2+ shuttled into LLC-PK1 cells using the ionophore, pyrithione. Moreover, when proteomic Zn2+ was liberated by the reaction with sulfhydryl binding reagents, NEM and diethylamine NONOate (DEA-NO), in the presence of Newport Green, insignificant amount of Zn-NPG was detected. By contrast, the higher affinity Zn2+ sensor (Kd  0.7 nM) than Newport Green, ZP1 formed ternary adduct Proteome•Zn-ZP1 with the dynamic Zn2+, where Zn2+ is adventitiously bound to proteome’s high affinity zinc binding sites. Besides with the mobile Zn2+, ZP1 also seems to react with the static distribution of cellular Zn2+ in specific Zn-proteins and generates ZP1-Zn-Proteome ternary adduct. Therefore, the effectiveness of the sensors to bind the cellular dynamic Zn2+ is a variable of proteome’s Zn2+ binding characteristics.
Keywords: Cellular Zinc Buffering; Newport Green; Zinc Fluorescent Sensors; Zinc Proteome; Zinc Trafficking; Zinpyr-1